Political identities and popular uprisings in the Middle East - Holliday, Shabnam J.; Leech, Philip 1984- (Rowman & Littlefield International, 2016)
"Explores the articulation of identity in the context of popular uprisings in the Middle East, going beyond a focus on the Arab Spring"--Provided by publisher.